2016
DOI: 10.1111/cga.12114
|View full text |Cite
|
Sign up to set email alerts
|

Expression of peptide fragments from proADM and involvement of mitogen‐activated protein kinase signaling pathways in pulmonary remodeling induced by high pulmonary blood flow

Abstract: Pulmonary arterial hypertension (PAH) is a life-threatening disease characterized by progressive pulmonary arterial remodeling and right ventricular failure. Despite recent advances in pathophysiological mechanism exploration and new therapeutic approaches, PAH remains a challenging condition. In this study, we investigated the roles of the peptide fragments from proadrenomedullin (proADM) such as adrenomedullin (ADM), adrenotensin (ADT), and proadrenomedullin N-terminal 20 peptide (PAMP) during pulmonary remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Besides the TGF-β/Smad2 signaling axis, multiple pathways have been reported to role in pulmonary remodeling. For example, Li et al showed that inhibition of MAPK-ERK signaling can reverse high pulmonary blood flow induced pulmonary remodeling [ 31 ]. Moreover, CaMK II was found to promote pulmonary remodeling by exerting its enzyme activity on catalyzing a series of serine or threonine residues in other proteins [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the TGF-β/Smad2 signaling axis, multiple pathways have been reported to role in pulmonary remodeling. For example, Li et al showed that inhibition of MAPK-ERK signaling can reverse high pulmonary blood flow induced pulmonary remodeling [ 31 ]. Moreover, CaMK II was found to promote pulmonary remodeling by exerting its enzyme activity on catalyzing a series of serine or threonine residues in other proteins [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight days later, the rats were weighed (body weight, BW) and anaesthetized by intraperitoneal injection of sodium pentobarbital (40 mg/kg). As described in the previous study (Li et al 2016), a catheter was inserted into the pulmonary artery of the rat and the RV systolic pressure (RVSP) was measured according to the waveform shown on the biological function laboratory system (BL-420, Tai Meng Technology Co., Ltd., Chengdu, China). After RVSP was measured, the hearts were removed from the anaesthetized rats and placed in cold normal saline.…”
Section: Hemodynamic Evaluationmentioning
confidence: 99%
“…Recent studies revealed that the process of pulmonary blood vessel formation and remodelling involves multiple signalling pathways, including the mitogen-activated protein kinase (MAPK) signalling pathway, nuclear factor-κB (NF-κB) signalling pathway, and PI3K/AKT signalling pathway (Li et al. 2014 ; 2016 ; Wang et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, ECM deposition and perivascular inflammation have been demonstrated to exert great influence in the pathogenesis of PaH (4,6). Furthermore, multiple reports have demonstrated that certain pathways, including erK and nF-κB, are associated with ECM deposition and inflammation in PAH, providing potential therapeutic targets for PaH (7,8).…”
Section: Introductionmentioning
confidence: 99%